(untitled) (Journal of Enam Medical College, 2021)
Infiltration of sarcoid granuloma in old cutaneous scars is one of the uncommon cutaneous manifestations of sarcoidosis. Here we report the case of a 32-year-old female who presented with swelling and irritation in a 9-month-old appendicectomy scar. An incisional scar biopsy was done and it revealed non-caseating granuloma. On query she had inflammatory polyarthritis and persistent dry cough for last two months. High resolution CT (HRCT) revealed right paratracheal, both hilar, paraaortic, and subcarinal lymphadenopathy with pulmonary nodular densities in both lung fields. FNAC from mediastinal node revealed non-caseating granuloma consistent with sarcoidosis. Successful regression of cutaneous inflammation was achieved using a course of oral steroids, hydroxychloroquine and methotrexate. The incidence of scar sarcoidosis is rare and therefore not well-understood. However, inflammatory alterations in preexisting scars may be important indicators of disease onset. J Enam Med Col 2020; 10(2): 122-125